2019
DOI: 10.1021/acsenergylett.9b00843
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Quantum Efficiency of Polymer Solar Cells with Efficient Exciton Splitting and Long Carrier Lifetime by Molecular Doping at Heterojunctions

Abstract: Optimizing the photovoltaic processes directly by electric technique attracts the exploration of molecular doping in organic photovoltaics (OPVs). However, the inappropriate and inhomogeneous dopant distribution in the bulk heterojunction (BHJ) film inhibits the performance improvement and mechanism understanding in doped OPVs. A strategy to solve these critical problems is reported here. By employing a planar heterojunction (PHJ) device structure, the role of dopant location and photovoltaic performance is cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 53 publications
1
63
0
2
Order By: Relevance
“…19,20 In any case, Yan et al have successfully used BCF as molecular dopant in a donor:acceptor planar heterojunction device structure and found that LA doping plays a synergistic role in changing the opto-electronic properties and nanomorphology of the blends leading to improved device performances, even at low doping concentration. [21][22][23] Consistent with the work of Doerrer and Green, 14 it has been suggested that some particular polymers like poly-cyclopentadithiophene-benzothiadiazole (PCPDTBT) can be also oxidized by BCF(OH 2 ) via an initial protonation step of the cyclopentadithiophene (CPDT) unit in the polymer backbone. In ref.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…19,20 In any case, Yan et al have successfully used BCF as molecular dopant in a donor:acceptor planar heterojunction device structure and found that LA doping plays a synergistic role in changing the opto-electronic properties and nanomorphology of the blends leading to improved device performances, even at low doping concentration. [21][22][23] Consistent with the work of Doerrer and Green, 14 it has been suggested that some particular polymers like poly-cyclopentadithiophene-benzothiadiazole (PCPDTBT) can be also oxidized by BCF(OH 2 ) via an initial protonation step of the cyclopentadithiophene (CPDT) unit in the polymer backbone. In ref.…”
Section: Introductionmentioning
confidence: 75%
“…However, this is likely to be very challenging as, even in solution, 1 H and 19 F NMR spectroscopies are unable to reliably distinguish between BCF(OH 2 ) n complexes with different n, 54 while neither the 11 B nor 19 F NMR spectra of [BCF(OH)BCF] À differ signicantly from that of [BCF(OH)(OH 2 )BCF] À in solution. 22 Finally we note that the non-straightforward doping nature of the BCF-induced doping process potentially complicates predictions regarding its applicability to other semiconductors. Although variations of the thermodynamic feasibility of the proposed overall p-doping reaction (Scheme 2, but with a complex counterion) for different semiconductors will depend only on the IP of the semiconductor, the kinetic feasibility is expected to depend critically on the ability to protonate the semiconductor.…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы использование низкомолекулярных органических допантов часто применяется для корректировки (тюнинга) электронных состояний полимерной матрицы, позволяющей повышать эффективность транспорта тех или иных носителей заряда в органических гетероструктурах [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Это особенно характерно при поиске путей повышения эффективности излучательной рекомбинации экситонов в многослойных электролюминесцентных устройствах, включающих в себя большое количество границ раздела разных материалов [9,10]. Как правило, в описанных выше случаях модификации подвергаются органические материалы с делокализованными валентными π-электронами на основе сопряженных соединений [1][2][3][4][5][6][7]9,10].…”
Section: Introductionunclassified
“…Это особенно характерно при поиске путей повышения эффективности излучательной рекомбинации экситонов в многослойных электролюминесцентных устройствах, включающих в себя большое количество границ раздела разных материалов [9,10]. Как правило, в описанных выше случаях модификации подвергаются органические материалы с делокализованными валентными π-электронами на основе сопряженных соединений [1][2][3][4][5][6][7]9,10]. Однако не меньший интерес могут представлять органические соединения с большой шириной запрещенной зоны, к которым относятся несопряженные полимеры [8,[11][12][13][14][15][16][17][18].…”
Section: Introductionunclassified
“…Compared to other photovoltaic devices, OSCs can be easily fabricated using solution processing methods on flexible substrates, giving the advantages of light weight and large-area fabrication [1,2,3,4,5]. With the continuous efforts on materials synthesis, morphology control, and device structure optimization, the power conversion efficiency (PCE) of OSCs has reached over 15% very recently [6,7,8,9]. All-polymer solar cells (All-PSCs), which employ conjugated polymers as both donor and acceptor, are becoming one of the most important candidates with many advantages.…”
Section: Introductionmentioning
confidence: 99%